Performance of cross-layer design for orthogonal space-time block coded MIMO systems with imperfect CSI in Ricean fading channels - Yu, Xiangbin; Zhou, Tingting; Liu, Xiaoshuai; Liu, Yan; Xu, Dazhuan (Telecommunication systems, 2014)
A cross-layer design (CLD) scheme for orthogonal space-time block coded MIMO systems with imperfect channel state information is presented by combining adaptive modulation and automatic repeat request, and the corresponding system performance is investigated over Ricean fading channel. The fading gain value is partitioned into a number of regions by which the modulation is adapted in terms of the region the fading gain falls in. The fading gain switching thresholds subject to a target packet error rate (PER) constraint are derived. According to these results, and using the generalized Marcum Q -function, we derive the theoretical formulae of average PER and spectrum efficiency (SE) of the system with CLD for both perfect and imperfect estimation in detail. As a result, closed-form expressions for average PER and SE are obtained. These expressions include some existing expressions in Rayleigh channel as special cases. With these expressions, the system performance in Ricean channel with perfect and imperfect estimation information can be evaluated effectively. Computer simulation for average PER and SE show that the theoretical analysis and simulation are consistent. The results show that the system performance will be effectively improved as Ricean factor increases, but it will be degraded as estimation errors increases.